The Effect of Varying Concentrations of Mugwort Leaf Extract (Artemisia vulgaris L.) on SPF and Cream Physical Stability - Umi Nafisah; Adeta Selvia Devi; Iin Suhesti (MEDFARM: Jurnal Farmasi dan Kesehatan, 2026)
Mugwort (Artemisia vulgaris L.) has antioxidant activity that can neutralize free radicals on the skin and also has sunscreen activity to protect the skin from UV exposure. This study highlights the benefits of the mugwort plant, which are currently unknown to the general public, requiring investigation into the formulation of its topical cream. This research aims to determine the stability of mugwort leaf extract cream and its SPF value. The extraction process uses the maceration method with 96% ethanol as the solvent. This study employed variations in mugwort leaf extract concentrations across formulas, starting from the control at 0% extract and increasing to 0.5%, 1%, 1.5%, and 2%. The organoleptic test results of the cream in the control formula showed a white color and green color in F1 to F4, with a characteristic smell and a semi-solid texture. The physical quality test for homogeneity indicates that all formulas are homogeneous. The pH test results of the formulation obtained values of 4,74-5,49, which meet the skin pH standard. The spreadability results obtained values of 6,15-6,38 cm. The cream's viscosity was in the range of 4,870-4,950 cPs. The hedonic test results showed that panelists preferred F1 with an extract concentration of 0.5%. The SPF test yielded scores ranging from 6,45 to 14,71. All formulations were able to preserve the physical quality stability of the preparations, according to the findings of the stability test conducted using the cycling test.